The new base excision repair pathway in mammals mediated by tyrosyl-DNA-phosphodiesterase 1 - Lebedeva, N.A.; Rechkunova, N.I.; Lavrik, O.I. (Вiopolymers and Cell, 2012)
Human tyrosyl-DNA phosphodiesterase 1 (Tdp1) hydrolyzesthe phosphodiester bond at a DNA 3' end linked to a tyrosyl moiety and has been implicated in the repair of Topoisomerase I (TopI )-DNA covalent complexes. Tdp1 can also hydrolyze other 3' end DNA alterations including 3' phosphoglycolate and 3' abasic (AP) sites, and exhibits the 3' nucleosidase activity indicating that it may function as a general 3' end-processing DNA repair enzyme. Recently we have shown a new Tdp1 activity generating DNA strand break with the 3' phosphate termini from the AP site. AP sites are formed spontaneously and are inevitable intermediates during base excision repair of DNA base damages. AP sites are both mutagenic and cytotoxic, and key enzymes for their removal are AP endonucleases. However, AP endonuclease independent repair, initiated by DNA glycosylases performing beta, delta-elimination cleavage of the AP sites, has been described in mammalian cells. Here, we describe another AP endonuclease independent repair pathway for removal of AP sites that is initiated by tyrosyl phosphodiesterase Tdp1. We propose that repair is completed by the action of a polynucleotide kinase, a DNA polymerase and finally a DNA ligase to seal the gap
Keywords: base excision repair, AP site, tyrosyl-DNA phosphodiesterase 1. Тирозил-ДНК-фосфодіестераза 1 (Tdp1) людини гідролізує 3'-фосфотирозильні зв’язки, які утворюються in vivo в результаті приєднання до ДНК-топоізомерази I (TopI). Tdp1 людини також здатна видаляти з 3'-кінця ДНК інші модифікувальні групи, включаючи 3'-фосфогліколати і залишки дезоксирибози, тобто функціонувати як 3'-фосфодіестераза і фермент репарації. Недавно ми показали, що Tdp1 людини притаманна ще одна активність – вона може гідролізувати апуринові/апіримідинові (АР) сайти всередині ланцюга ДНК з утворенням 3'-кінцевого фосфату. АР-сайти – це одне з найчастіше виникаючих пошкоджень ДНК. Ключовим ферментом, який розщеплює АР-сайти, є апуринова/апіримідинова ендонуклеаза 1 (АРЕ1). Проте в клітинах ссавців існує шлях репарації, незалежний від АРЕ1, у якому беруть участь ДНК-глікозилази. У даній роботі описано ще один АРЕ1-незалежний шлях репарації АР-сайтів за участі Tdp1. До повного циклу репарації залучені полінуклеотидкіназа/фосфатаза, яка має 3'-фосфатазну активність, ДНК-полімераза та ДНК-лігаза.
Ключові слова: ексцизійна репарація основ, АР-сайт, тирозил-ДНК-фосфодіестераза 1. Тирозил-ДНК-фосфодиэстераза 1 (Tdp1) человека гидролизует 3'- фосфотирозильные связи, образующиеся in vivo в результате присоединения к ДНК-топоизомеразе I (TopI). Tdp1 человека также способна удалять с 3'-конца ДНК другие модифицирующие группы, включая 3'-фосфогликолаты и остатки дезоксирибозы, т. е. функционировать как 3'-фосфодиэстераза и фермент репарации. Недавно мы показали, что Tdp1 человека обладает еще одной активностью – она может гидролизовать апуриновые/апиримидиновые (АР) сайты внутри цепи ДНК с образованием 3'концевого фосфата. АР-сайты – это одно из наиболее часто возникающих повреждений в ДНК. Ключевым ферментом, расщепляющим АР-сайты, является апуриновая/апиримидиновая эндонуклеаза 1 (АРЕ1). Однако в клетках млекопитающих существует путь репарации, независимый от АРЕ1, с участием ДНК-гликозилаз. В данной работе описан еще один АРЕ1-независимый путь репарации АР-сайтов с участием Tdp1. В полный цикл репарации вовлечены полинуклеотидкиназа/фосфатаза, обладающая 3'-фосфатазной активностью, ДНК-полимераза и ДНК-лигаза.
Ключевые слова: эксцизионная репарация оснований, АР-сайт, тирозил-ДНК-фосфодиэстераза 1.